SUMBER POKOK HUKUM ISLAM (ANALISIS AL-QUR’AN DAN AL-HADIS) - M Choirul Muzaini; Mahmud Arif (STKIP Subang, 2023)
State life and governance cannot be separated from the rule of law. As a religious organisation, it is necessary to follow the rules set out in the teachings, just as Islam has rules and regulations that must be followed by its followers. This research aims to describe the Basic Sources of Islamic Law (Analysis of Al-Qur'an and Al-Hadis). This research is a qualitative research with literature review type. Information collection is carried out by looking for several important sources including primary sources from literature sources that discuss the Basic Sources of Islamic Law (Analysis of the Qur'an and Al-Hadith) and several other literature sources related to the research. The data collected was then analysed so as to obtain the results of the study which showed that the sources of law in Islam are the Qur'an and As-Sunnah, the words of God and the As-Sunnah of the Prophet which are the basic principles of Islamic teachings. Understanding these two sources of law is important because they are not separate, there is a connection between them in defining the laws that apply to Islam. Therefore, it is important to understand both legal texts, if there is a misunderstanding between the two, it will damage the existence of the legal cause. By understanding the two sources of law, namely the Qur'an and Hadith, one will get legal advice according to the guidance of the Sharia and the Sunnah of the Prophet Muhammad SAW. This article describes the existence of two sources of Islamic law in its application to the general public, using a thematic approach.